Detection of Wolbachia in Mosquitoes (Diptera: Culicidae) in the State of Maranhão, Brazil. Issue 5 (15th July 2022) - Chaves, Erick Barros; Nascimento-Pereira, Agostinho Cardoso; Pinto, Jorge Luiz Moraes; Rodrigues, Bruno Leite; de Andrade, Marcelo Souza; Rêbelo, José Manuel Macário
Abstract: Recently, the endobacteria Wolbachia has emerged as a biological tool for the control of arboviruses. Thus, we investigated the rate of natural infection by Wolbachia in Culicidae species from Maranhão, Brazil. For this, we amplified the Wolbachia surface protein gene ( wsp ) from mosquitoes collected in six localities of Maranhão, and positive samples were subjected to new analysis using group-specific primers. In total, 448 specimens comprising 6 genera and 18 species of mosquitoes were analyzed. Wolbachia DNA was PCR-detected in 7 species, three of which are new records: Aedes scapularis (Rondani, 1848), Coquillettidia juxtamansonia (Chagas, 1907) and Cq. venezuelensis (Theobald, 1912), in addition to Ae. albopictus (Skuse, 1894) and Culex quinquefasciatus Say, 1823, which are commonly described as permissive to maintain this bacterium in natural environments, and two species of the subgenera Anopheles ( Nyssorhynchus ) Blanchard, 1902 and Culex ( Melanoconion ) Theobald, 1903 which could not be identified at species level. The infection rate of all species ranged from 0 to 80%, and the average value was 16.5%. This study increases the knowledge about the prevalence of Wolbachia in the culicid fauna and may help in selecting strains for biological control purposes.